Antiviral activity of nitazoxanide against Morbillivirus infections - Debora Stelitano; Simone La Frazia; Annalisa Ambrosino; Carla Zannella; Daniel Tay; Valentina Iovane; Serena Montagnaro; Anna De Filippis; Maria Gabriella Santoro; Matteo Porotto; Massimiliano Galdiero (Elsevier, 2023)
The measles virus (MeV) and canine distemper virus (CDV) belong to the genus Morbillivirus of the Paramyxoviridae family. They are enveloped viruses harboring a non-segmented negative-sense RNA. Morbilliviruses are extremely contagious and transmitted through infectious aerosol droplets. Both MeV and CDV may cause respiratory infections and fatal encephalitis, although a high incidence of brain infections is unique to CDV. Despite the availability of a safe and effective vaccine against these viruses, in recent years we are witnessing a strong resurgence of Morbillivirus infection. Measles still kills more than 100,000 people each year, and CDV causes widespread outbreaks, especially among wild animals, including non-human primates.No drugs are currently approved for MeV and CDV. Therefore, the identification of effective antiviral agents represents an unmet medical need. Here, we have investigated the potential antiviral properties of nitazoxanide (NTZ) against MeV and CDV. Antiviral activity was explored with live virus and cell-based assays. NTZ is a thiazolide that is approved by the FDA as an antiprotozoal agent for the treatment of Giardia intestinalis and Cryptosporidium parvum. Further, nitazoxanide and its metabolite tizoxanide have recently emerged as broad-spectrum antiviral agents. We found that NTZ blocks the MeV and CDV replication, acting at the post-entry level. Moreover, we showed that NTZ affects the function of the viral fusion protein (F), impairing viral spread. Our results indicate that NTZ should be further explored as a therapeutic option in measles and canine distemper virus treatment.